Stigmatization of human immunodeficiency virus (HIV) positive patients by health care workers at King Edward VIII Hospital, Durban, Kwa-Zulu Natal - Famoroti, Temitayo O. (My University, 2011)
INTRODUCTION: The human immune deficiency virus (HIV) leads to the acquired immune deficiency syndrome (AIDS). AIDS was first identified in the 1980’s and since then has spread globally causing one of the most dreaded pandemics of modern time. The issue of stigma is very important in the battle against HIV/AIDS as it affects attendance at health centres for obtaining ARV and regular medical check-ups, adherence of patients to ARV treatment. The fear of stigma further helps to fuel a culture of secrecy, silence, ignorance, blame, shame and fear of victimization. AIM: The aim of this study was to determine if there was any external stigmatization of HIV positive patients by health care workers (HCWs) at King Edward VIII Hospital. OBJECTIVES: To determine if the knowledge of HCWs regarding HIV/AIDS and its transmission affect the way they supply a service towards HIV positive patients at King Edward VIII Hospital and to determine the comfort level and the attitude of the HCWs in rendering care to a HIV positive patient. METHODOLOGY: This was a cross sectional survey where data was collected using an anonymous selfadministered structured questionnaire with closed ended questions on personal and professional characteristics, disease knowledge, and discriminatory practices such as attitudes and comfort levels towards people living with HIV/AIDS (PLWHA). A total of three hundred and thirty four HCWs from different units at the King Edward VIII hospital participated in this study. FINDINGS Overall the HCWs have an above average knowledge about HIV/AIDS and its transmission with only 1.8% scoring below average in the knowledge questions regarding HIV and its transmission, although some knowledge gaps were identified regarding occupational exposure risks. Evidently from the results is that HCW with higher levels of education are more knowledgeable on issues relating to HIV/AIDS. The implication is that a HCW with a better education is better equipped with the cognitive knowledge to deal with HIV/AIDS, highlighting iv the importance of education related to external stigmatization. Even though HCWs were knowledgeable about HIV/AIDS most still felt uncomfortable in performing some occupational duties on PLWHA like assisting a woman in labour and performing invasive surgical operations. Most of the HCWs showed a positive attitude towards PLWHA believing that they are not to be blamed for their condition but that individuals in the community who are perceived to be promiscuous men or women are the ones responsible for the spread of HIV/AIDS. Procedures like patients being tested without their consent and patients required to do a HIV/AIDS test before surgery that could be perceived as stigmatization have been observed in King Edward VII hospital. Patient confidentiality is also compromised in that gossiping by HCWs about the HIV/AIDS results of patients has been noted. Fortunately a significant number of HCWs are willing to report their colleagues to a higher authority if any form of stigmatization or discrimination towards PLWHA is seen at King Edward VIII Hospital. CONCLUSION Although the knowledge, attitude and comfort of the HCWs at King Edward VIII Hospital was above average continuing medical education and continuing professional development should be mandatory in the management of HIV/AIDS so that HCWs can have the needed knowledge to keep up with the changing world of HIV/AIDS medicine and also about universal precautions to take so as to reduce occupational exposures. Psychological support to the HCW is needed in dealing with PLWHA so that patients can be provided with quality and compassionate care irrespective of their HIV/AIDS status as this will eventually help in the reduction of stigma.
Thesis (MPH)--University of Limpopo, 2011.
Keywords: AIDS; HIV